Réponses

  • Utilisateur Brainly
2014-03-27T20:52:38+01:00
3(2× +4)- 5 =6x+7
                                                                                                                     -3(1+2y)+3y =-3y-3
                                                                                                                    
7(3a -1)+5a =26a-7
                                                                                                                      
5b(1-b)- 2b
  =-5b²+3b
2014-03-27T20:52:54+01:00
3(2x+4)-5 = 6x+12-5 = 6x +7

-3(1+2y)+3y = -3-6y+3y = -3 -3y

7(3a-1)+5a = 21a-7 + 5a = 26a-7

5b(1-b)-2b = 5b-5b² -2b = -5b² +3b